Biological Difference Between Epstein–Barr Virus Positive and Negative Post-transplant Lymphoproliferative Disorders and Their Clinical Impact - Ferla, Valeria; Rossi, Francesca Gaia; Goldaniga, Maria Cecilia; Baldini, Luca (Frontiers in Oncology, 2020)
Epstein-Barr virus (EBV), an oncogenic human virus, is associated with several lymphoproliferative disorders, including Burkitt lymphoma, Hodgkin disease, diffuse large B-cell lymphoma (DLBCL), and posttransplant lymphoproliferative disorder (PTLD). The oncogenic Epstein-Barr virus (EBV), present in 80% of PTLDs, has a causative role in the oncogenic transformation of lymphocytes and influences immune responses. Because the development of PTLD is the consequence of an imbalance between immunosuppression and immunosurveillance, different approaches can be justified for treating this disorder, including reduction of immune supression, destruction of the malignant clone, and suppression of the EBV viral load. In more aggressive forms of PTLD, upfront chemotherapy may offer a better and more durable response. The aim of this review is to characterize the clinicopathological and molecular-genetic characteristics of PTDL and to elucidate whether EBV(+) and EBV(−) PTLD are biologically different. Gene expression profiling, next-generation sequencing and microRNA profiles have recently provided plethora of data shedding light on pathogenic mechanisms sustain PTLDs and identifying potential vulnerable mechanisms to be explored therapeutically. This article aims to explore the entity of EBV(–)PTLD, the new insights into the pathogenesis, the clinical behavior of EBV(+)PTLD with the hope to offer theoretical support for future therapeutic study.